Numerical and experimental studies of compression-tested copper, mortar contact method (2017)
Simulation of compression test of copper is made with the mortar contact method and assuming: axial symmetry, multiple point constraint of type plane, concentrate load and coulomb friction. Copper is simulated like isotropic material, elastic until it yields stress, and then like a hardening material with incremental plasticity. Copper behavior was calculated from experiments. Seventeen compression tests without lubrication were carried out to cylindrical samples at room temperature. The Stress vs. Strain relationship was calculated using two friction corrections; the Rowe Correction and the Dieter Correction. It was concluded that the simulation made with the mortar contact method and the Dieter Correction is a good alternative to simulate the compression test, being the differences between the simulation and the experiments lower than 7.33%, the hypothesis of axial symmetric does not keep away the simulation of the reality and new numerical analysis will allow the development of better friction corrections.